Safety of Continued Clopidogrel Use in the Preoperative Course of Gastrointestinal Surgery: A Retrospective Cohort Study. Issue 2 (February 2017) - Jupiter, Daniel C.; Fang, Xiao; Adhikari, Deepak; Mehta, Hemalkumar B.; Riall, Taylor S.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Our study aimed to estimate postoperative bleeding risk in older adults taking clopidogrel before gastrointestinal (GI) surgery, to aid surgeons in decisions regarding clopigogrel cessation. Summary Background Data: Balancing risks of postoperative bleeding associated with continued clopidogrel use and those associated with cessation is difficult for GI surgeons. Methods: Using 100% Texas Medicare Claims Data from 2006 to 2011, we identified patients undergoing emergent GI surgery. We propensity score matched patients on clopidogrel before surgery to patients not on clopidogrel. Using conditional logistic regression, we compared risks of bleeding events at 1-month postdischarge between groups, adjusting for bleeding risk factors. Results: In total, 1240 patients undergoing emergent GI surgery while treated with clopidogrel were matched to emergency GI surgery patients not treated with clopidogrel. The only significant preoperative differences between groups were higher percent of clopidogrel-treated patients with congestive heart failure, cholecystectomy, and lower percent of clopidogrel-treated patients with colectomy. Mean age was 76.91 (±7.06) and 76.70 (±7.05) years ( P = 0.47), and 63.84% and 59.41% of operations were cholecystectomy, in the clopidogrel and nonclopidogrel groups ( P = 0.18). In multivariable analyses adjusting for Elixhauser index, hyperlipidemia, confounding drugs, and surgery type, odds ratio for bleeding within 30 days of discharge in those exposed to clopidogrel compared with those not exposed was 1.60 (95% confidence interval, 1.08–2.38), with raw rates of bleeding 6.85% and 4.84%. Conclusions: Clopidogrel use in older adults through the preoperative period of GI surgery does not significantly increase bleeding events in the month after surgery.